Analysis of Genetic Variations in bHLH Protein (Rc) Gene Sequences in Rice (Oryza) NCBI PopSet 2496581476 Using In-Silico RFLP: Analisis Variasi Genetik Sekuen Gen Rc-bHLH Protein pada Padi (Oryza) NCBI PopSet 24596581476 Menggunakan RFLP secara In-Silico - Hasanah, Nurul; Violita, Violita; Achyar, Afifatul (Genetikawan Muda Indonesia, 2023)
Rice is a plant from the Graminae Family that is spread almost throughout the region. In rice, there is an Rc gene that codes for the formation of the basic loop-helix-loop (bHLH) protein, the Rc gene (Rc-bHLH) functions as a transcription of color pigments in brown rice. This research was conducted computationally from several related sites. The study used restriction enzyme BstUI with a side recognition of 5'-CG'CG-3'. The purpose of this study was to analyze the genetic variation of the Rc gene sequence encoding the bHLH protein in NCBI PopSet rice 2496581476 using RFLP in silico. The results showed that there were genetic variations of the Rc-bHLH gene, 2 allele variations were present in 21 rice sequences using the restriction enzyme BstUI.